Whiteness and Masculinity in Nonprofit Organizations: Law, Money, and Institutional Race and Gender. Issue 3 (3rd July 2019) - Heckler, Nuri
Abstract : Using an institutional framework and critical race and gender theories, this article argues that performances adopted by nonprofits to conform to the legal and economic realities of the sector benefit Whites and men. Economic and legal influences on nonprofits create pressures to conform to the institutions that organize society. Whiteness and Masculinity are two such institutions. After establishing theoretical propositions, the conclusion poses questions to aid in furthering research on Masculinity and Whiteness in nonprofits and undermine the forces frustrating race and gender equity in the nonprofit sector.